Drawing and design - Fernandez, Sergio (Risco - Journal of Architecture and Urbanism, 2018)
The paper explains the teaching methodology forarchitectural design applied in the first year of the Faculdadede Arquitectura of the Universidade do Porto, based on ananalogy between the professional practice and the learningprocess. Without wishing to set out strict rules when categorizing the most relevant aspects related to the drawing in thearchitectural field, it aims to emphasize the inextricable relation between Drawing and Architectural Design, as well asthe role of the first in the visual education and the architect’scorresponding qualification.